Teaching visually impaired learners through ICTs: lessons from teachers’ perceptions in a full-service school - Serero, Pule; Phala, Thembi; Mahlo, Dikeledi (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
An international shift towards inclusivity has prompted the use of Information Communication Technologies (ICTs) to teach Visually Impaired Learners (VILs) accommodated in Full-Service Schools (FSSs). This paper explores teachers’ perceptions of using ICTs to teach VILs in a Full-Service School (FSS). The study adopted a qualitative case study design while nested within the interpretive paradigm. Focus group interviews, observations and document analysis were triangulated to collect data. Purposive sampling was conducted to identify suitable teachers, and subsequently, four focus groups consisting of five teachers (20 in total) each were conducted. Generated data were analysed thematically. Despite the positive perceptions towards using ICTs to teach VILs, teachers experience challenges when using ICTs to teach VILs. We recommend that the school procure adequate and various ICTs used to teach VILs.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 2, Volume 9, 2025
Keywords: Information Communication Technologies; Visually Impaired Learners; Full-Service School; Inclusive Education; Inclusive education; People with visual disabilities; Computer-assisted instruction; Educational technology